ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUTRATIO (Studi Kasus Pada Perusahaan LQ-45 Yang Terdaftar Di BEI Periode 2013-2015) - Ayu Novitasari, 13.05.51.0215 (Students Journal of Economic and Management, 2017)
The Purpose of study is to examine and analyze the factors that effect the Dividend Payout ratio in LQ 45 companies. The population of this research are companies included in the category LQ 45 2013-2015. The sampling technique is done by purposive sampling. Based on the results of the sampling purposive obtained a sample of 81 companies. The results of this study show each variable has influence varies is Institutional Ownership and Liquidity positive effect on Dividend Payout Ratio, Growth of Companies negative effect on Dividend Payout Ratio, and Profitabilities positive effect was not significant to Dividend Payout ratio. Adjusted R^2 value is 0,640 this means that 64% of the dependent variable can be explained by the independent variable, while the remaining 36% is explained by other causes outside the model. Key Word : Institutional Ownership, Growth of Companies, Liquidity, Profitabilities and Dividend Payout Ratio